Resting cortical brain activity and social behavior in higher functioning children with autism. - Sutton, Steven K.; Burnette, Courtney P.; Mundy, Peter C. (Journal of Child Psychology & Psychiatry & Allied Disciplines., 2005)
Background: Psychophysiological measurement of processes related to social behavior may be valuable for research on individual differences and subgroups among children with autism spectrum disorders (Coleman, 1987; Dawson, Klinger, Panagiotides, Lewy, & Castelloe, 1995; Modahl et al., 1998). In particular, recent research and theory suggests that measures of resting anterior EEG asymmetry reflect complex brain processes associated with individual differences in approach or avoidance motivation that may be associated with social and emotional interaction tendencies among children with autism. Method: This hypothesis was examined in a study of the relations among resting anterior asymmetry, social impairment, and social anxiety in 23 high functioning children with autism (HFA) and 20 controls (age range 9-14 years). Results: These groups were significantly different on the measures of anterior asymmetry, social symptoms and anxiety-related measures. Moreover, HFA children who displayed right frontal asymmetry (RFA group) displayed more symptoms of social impairments and better visual analytic skills than did children who displayed left frontal asymmetry (LFA group). Alternatively, while the LFA group displayed fewer symptoms of social impairment they also reported greater levels of social anxiety, social stress, and lower satisfaction with interpersonal relations than did the RFA group. Conclusions: These observations indicate that anterior EEG asymmetry may be a marker of motivation and emotion processes that refract the autism taxon into important individual differences in social presentation among higher functioning children. Reprinted by permission of the publisher.